Information disclosure behaviour in social media among Malaysian youth : the impact of privacy concern, risk and trust - Norsaremah Salleh,; Ramlah Hussein, *; Umar Aditiawarman, (2011)
People have been using Social Network Sites (SNS) to communicate and make friends through online. Although SNS has been benefited its users in many ways, information privacy seemed to be overlooked. This study proposes a framework to examine users? protective behaviour associated with information disclosure in SNS. The proposed framework was derived based on the Protection Motivation Theory and Privacy Concern.